Innovative financing for health: what are the options for South Africa? - Robert J. Fryatt (AOSIS, 2012)
The paper assesses the options for additional innovative financing that could be considered in South Africa, covering both raising new funds and linking funds to results. New funds could come from: i) the private sector, including the mining and mobile phone industry; ii) from voluntary sources, through charities and foundations; iii) and through further expanding health (sin) levies on products such as tobacco, alcohol and unhealthy food and drinks. As in other countries, South Africa could earmark some of these additional sources for investment in interventions and research to reduce unhealthy behaviors and influence the determinants of health. South Africa could also expand innovative linking of funds to improve overall performance of the health sector, including mitigating the risks for non-state investment and exploring different forms of financial incentives for providers and patients. All such innovations would require rigorous monitoring and evaluation to assess whether intended benefits are achieved and to look for unintended consequences.